TANGGUNG JAWAB PEMULIHAN HAK KONSUMEN YANG DIRUGIKAN BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Vasya Hana Namira; N.G.N Renti Maharaini (Jurnal Riset Multidisiplin Edukasi, 2025)
The meikarta development process has experienced several cases that have made the construction late until now, not only that, some standard clauses contained in the Affirmation and Approval of Unit Reservation (P3U) dated August 18, 2017, which is the PPJB in this case are often used by business actors to include exoneration clauses. The researcher apply the problem is of whether consumers can receive compensation and how the developer's responsibility for the delay in construction, and whether the P3U is proven to violate the GCPL. The research method is normative legal research, descriptive in nature, using secondary data made from primary, secondary, and tertiary legal materials, analyzed qualitatively, and drawing conclusions using deductive logic. Based on the analysis conducted, it is known that the P3U issued by the developer contains several standard clauses called exoneration clauses or prohibited clauses in accordance with Article 18 of the GCPL because they are detrimental to consumers. It is also known that consumers are entitled to receive compensation that must be implemented by the developer due to delays in construction in accordance with what has been stated in the P3U which in this case is a PPJB.